Evaluating the learning outcomes of interfaith initiatives: a systematic literature review - Visser, Hannah J. (Journal of beliefs and values, 2024)
Interfaith initiatives are seen as promising sites for societal change and personal transformation. However, many questions about the actual outcomes of such initiatives have remained unanswered. Therefore, a systematic review was conducted, focusing on 1) the outcomes of interfaith initiatives and 2) the methods used to evaluate these outcomes. This review analyses 47 empirical studies on interfaith initiatives. The review of the initiatives’ outcomes indicates that interfaith initiatives can positively impact participants’ knowledge about other worldviews, communication skills and appreciation for other worldviews. At the same time, it can be challenging for interfaith initiatives to positively impact participants’ knowledge of socio-political challenges, awareness of power imbalance and privilege and behaviour as interfaith leaders. The analysis of the methods used to evaluate the impact of interfaith initiatives shows that most studies used qualitative methods. For studies using quantitative or mixed methods designs, a variety of measurement instruments were used, whereby there was little overlap or consensus regarding the concepts being used. The findings of this article will stimulate scholars to focus more on learning activities and evaluation methods that take societal learning outcomes into consideration. It emphasises the need to build on previous evaluation and research efforts.